Urban Dendroflora of Dry Subtropics of the Northwestern Part of The Greater Caucasus on the Example of the City of Gelendzhik - Postarnak Yulia; Zhavoronkov V. V. (Russian Journal of Earth Sciences)
The article presents the results of the analysis of the species composition of the dendroflora of the city of Gelendzhik. The research covered 20 hectares of tree plantations. The route method and the transect method were used. In total, 30 transects were laid with a width of 5-20 m and the total length was 22 km. The routes covered all biotopes of natural (natural forest plantations on the outskirts of the city) and anthropogenic habitats (boarding houses, house territories of private households, spontaneous vegetation of roadsides and wastelands). True census of all tree and shrub species was carried out on the transects. Special attention was paid to rare species for which renewal and undergrowth were taken into account. The arboreal flora of Gelendzhik is represented by 110 species, which belong to 75 genera and 35 families. The predominant part of the dendroflora is represented by angiosperms (82.7%) and gymnosperms (13.7%). The families of Rosaceae, Cupressaceae and Fabaceae are most widely represented in the dendroflora of the city's green spaces (44%). The analysis of the species composition on their share of participation showed that the native fraction of the dendroflora prevails over the cultural one, which indicates its species richness. The analysis of the geographical element of the wild-growing fraction showed the heterogeneity of the dendroflora, in the formation of which 15 geographical elements take part. The largest number of species in the studied dendroflora belongs to the ancient Mediterranean group of geoelements. The significant participation of the Mediterranean and Caucasian geoelements indicates a high degree of autochthonicity in the development of the dendroflora of the city of Gelendzhik. Phanerophytes predominate among the life forms, represented equally by mesophanerophytes, nanophanerophytes and microphanerophytes. It should also be emphasized the significant participation of adventitious tree species (15.4% of the aboriginal fraction). Most of the adventitious species are of North American origin. The leading place in the quantitative spectrum is occupied by rare Mediterranean species Pinus brutia var. pityusa (Stev) Silba) (21% of the total number of studied individuals), Prunus mahaleb (L.) Vassilcz.) (7%), Pistacia atlantica Desf. (2.1%), which reflects the specifics of the dendroflora of the city of Gelendzhik.